Development of enzyme-linked immunosorbent assay for detecting Ornithobacterium rhinotracheale (ORT) infection in chicken - Adin Priadi; Lily Natalia (Jurnal Ilmu Ternak dan Veteriner, 2006)
Ornithobacterium rhinotracheale (ORT) has been recognized in chicken in Indonesia and incriminated as a possible additional causative agent in respiratory disease complex. An enzyme-linked immunosorbent assay (ELISA) has been developed for the seroepidemiological study of ORT infection in chickens. Ten weeks old chickens are injected with 0.5 ml of killed O.  rhinotracheale emulsified in Freund's complete adjuvant at a concentration of 109 CFU/ml. Hyperimmune sera and non-reactive control sera were used to standardized the ELISA for ORT infection. Optimum condition for the ORT ELISA was antigen dilution 1/800, serum dilution 1/100 and 1/4000 conjugate dilution. Optical density cut-off point was determined by using 31 serum samples from 2 broiler farms. Cut-off for negative serum was 0.27 (mean + 3 standard deviation). With these optima, 187 chicken sera from broiler, layer and broiler breeder farms were collected and screened. Seroconvertions were detected from broiler and layer farms in Magelang district, Central Java (Bojong I, Paremono, Bojong II, Keblukan) and a broiler breeder farm in West Java. The seraconvertion were 0, 10, 94, 88 and 100 percents respectively. These figures show that the prevalence of O. rhinotracheale infection in chicken in layer and breeder farms were very high. Key Words: Ornithobacterium rhinotracheale (ORT), ELISA, Chicken